Relationship quality and satisfaction in relation to compatibility of romantic partners' attachment styles - Kamenov, Željka; Jelić, Margareta; Tadinac, Meri Hromatko, Ivana; Pantić, Petra (2006)
The aim of our study was to determine if there is a compatibility between romantic partners’ attachment styles and if so, how it is related to relationship satisfaction, perceived quality of a relationship, as well as its’ stability. Our sample consisted of 418 adult heterosexual couples, partners’ age between 18 and 80. Participants answered a questionnaire consisted of a measure of attachment, relationship satisfaction, quality and stability. Results suggest that couples have compatible attachment styles to their partners. Individuals with secure attachment style also have partners with secure style, while individuals with inadequate attachment styles are in relationship with a partner who has a compatible insecure style. Two interpretations are considered: people chose partners with compatible attachment style or they adapt to the partner’ s attachment style during a relationship. In order to test these hypotheses, research is continued on young couples who just started dating.
Projekt MZOS
Projekt MZOS
ENG